Acting with Both Sides of Your Brain? Considering the Consequences of Adopting More Rigorous Psychological Languages in Acting Research - Banfield, Chris (Research in drama education, 2000)
The relationship between drama research and research in other disciplines is currently arousing considerable interest. The focus of this article is psychology and acting. Consideration is given to metaphorical languages of acting commonly to be found passing as 'psychological' perspectives. While acknowledging the importance of viewing all approaches to acting research, including the positivist and empirical, within the framework of the social and cultural contexts that produce them, a relativist position is rejected in favour of the need for greater scientific rigour in the use of such languages. By way of comparison, the work of cognitive psychologists Tony and Helga Noice on 'expertise' in professional acting is discussed. However, difficulties are revealed with the theoretical underpinnings of this research, specifically the psychologists' conception of what an 'expert actor' might be, notwithstanding their methodological sophistication and extensive production of research data. In conclusion, the issue of operationalisation of acting for research purposes is raised, and the need for approaches addressing procedural rather than declarative questions argued.